PENGARUH PERILAKU KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN KONAWE - Fatmah Yuyu Yuliana; Samdin Samdin; La Hatani (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
The purpose of this research is to examine and explain the influence of leadership behavior on employee performance mediated by organizational commitment and job satisfaction in the Konawe District PPKB Office. This research approach is a survey with explanatory research design. Data collection is done cross-section using instruments in the form of questionnaires. The population of this study is a Vertical ASN at the Konawe Regency PPKB Office with a sample of 63 people. The analysis equipment used for hypothesis testing is Partial least square (PLS). The results showed that leadership behavior have a positive and significant effect on commitment and job satisfaction, but on employee performance have not significant effect. Organizational commitment has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Furthermore, organizational commitment and job satisfaction serve as a perfect mediation on the influence of leadership behavior on employee performance. This means that good leadership behavior contributes significantly to improving organizational commitment and job satisfaction. Then organizational commitment and high job satisfaction then employee performance is significantly improved. However, direct leadership behavior does not contribute significantly to improving employee performance, unless it first increases organizational commitment and employee job satisfaction.